HOW PRIVACY, SECURITY, AND REPUTATION PERCEPTIONS INFLUENCE REPURCHASE INTENTION: MEDIATING ROLE OF TRUST IN SHOPEE - Miftahun Nadzir, Muhammad; Adam Fadilah, Rian (UIN Raden Mas Said Surakarta, 2025)
This study aims to find out how privacy, security, and reputation perceptions influence repurchase intention the mediating role of trust in Shopee. The object of this study was e-commerce with a total sample of 205 respondents selected using the purposive sampling method. Data analysis techniques in this study used structural equation modeling (SEM) with the AMOS 21.0 analysis tool. Based on the results of the study, it shows that perceptions of privacy, perceptions of security, and perceptions of reputation have a positive and significant effect on consumer confidence. Perceptions of privacy, perceptions of reputation, and perceptions of security have a positive and significant effect on repurchase intention. Consumer trust has a positive and significant effect on repurchase intention. Consumer trust mediates perceptions of privacy, perceptions of security, and reputational perceptions of repurchase intention. This research implies that systematically building trust is crucial, as it has been proven to be a mediating variable. This means that even if consumers have positive perceptions of privacy, security, and reputation, without strong trust, repurchase intention will not be optimal